VALIDITY OF 3D PAGEFLIP-BASED POCKET BOOK ABOUT PTERIDOPHYTA IN THE MANGROVE AREA, KURAU DISTRICT, SOUTH KALIMANTAN, INDONESIA - Saripah Alya Shavira; Dharmono Dharmono; Maulana Khalid Riefani (Universitas Negeri Padang, 2022)
Local potential, especially pteridophyte plants and based on local potential can be used as a source of learning, plant development based on local potential. Validity can be interpreted as an act of proving precisely through certain stages to achieve the desired results. The purpose of this study is the validity of the 3D Pageflip Pocket Book based on the Pteridophyta species, Kurau sub-district, validity. The study used a descriptive approach to research on Pteridophyta in the Mangrove Area. The results showed that the test of the validity of the expert's assessment obtained an average result that was very valid, namely 92.10%. Based on the scores obtained, the Pteridophyta species pocket book based on the 3D Pageflip developed is very valid.